Conceptualising Culture Wars in the Post-Communist Space: Latvia, the Istanbul Convention and the Struggle for Power. Issue 8 (14th September 2021) - Isaacs, Rico; Rudzite, Liga
Abstract: This essay establishes a framework for analysing culture wars in the post-communist space. Using Latvia's debate over the ratification of the Istanbul Convention on violence against women, it outlines the central features of culture wars: moralisation, externalisation of agency, the instrumentalisation of culture and the struggle for power and resources. While existing scholarship conceptualises culture wars as a dichotomous battle between the sacred and the secular, or between liberal and illiberal, our thematic analysis of the Istanbul Convention debate in Latvia finds it was less about culture and more a complex struggle between political and religious actors competing for power and resources.